Offspring production in three freshwater crab species (Brachyura: Pseudothelphusidae) from the Amazon region and Central America - Ingo S. Wehrtmann (Zoologia (Curitiba), 2010)
Freshwater crabs are an important component of the fauna of limnic environments, and out of the two true freshwater crab families present in the Neotropics, Pseudothelphusidae is the most diverse. Considering the lack of information regarding reproductive features of neotropical freshwater crabs, we studied, for the first time, the fecundity and the presence of juveniles carried by females of two pseudothelphusids from the Amazon region - Kingsleya latifrons (Randall, 1840) and Kingsleya ytupora Magalhães, 1986 - and one from Central America - Potamocarcinus magnus (Rathbun, 1896). The two Kingsleya species produced relatively few (56-114) and large eggs (1.9-3.7 mm), typical for species with an abbreviated or direct development. Recently produced eggs were substantially larger in K. latifrons (mean 2.83 mm) when compared to those of K. ytupora (mean 1.87 mm); however, at the end of the embryogenesis, mean egg diameter was similar in both species. Therefore, it is assumed that hatchlings in both species should have a similar size. A brief description of attached juveniles of K. ytupora is provided. The number of juveniles varied between 30 (K. ytupora) and 179 (P. magnus); two size groups of juveniles were found, which indicates that the offspring cling to their mother for a prolonged period of time. There was no significant loss of eggs and juveniles; it is assumed that parental care diminishes the loss of their offspring. We compiled the available information of reproductive aspects from freshwater crabs: egg diameter was in the range of 2-3 mm, independent of female size and fecundity, and reported egg number varied between 9 and 417 eggs.